Fibre electronics: towards scaled-up manufacturing of integrated e-textile systems. Issue 30 (22nd July 2021) - Seyedin, Shayan; Carey, Tian; Arbab, Adrees; Eskandarian, Ladan; Bohm, Sivasambu; Kim, Jong Min; Torrisi, Felice
Abstract : Advances in materials development, fabrication processes, and applications for various fibre electronics are reviewed. Their integration into multifunctional electronic textiles and the key challenges in large-scale manufacturing are discussed. Abstract : The quest for a close human interaction with electronic devices for healthcare, safety, energy and security has driven giant leaps in portable and wearable technologies in recent years. Electronic textiles (e-textiles) are emerging as key enablers of wearable devices. Unlike conventional heavy, rigid, and hard-to-wear gadgets, e-textiles can lead to lightweight, flexible, soft, and breathable devices, which can be worn like everyday clothes. A new generation of fibre-based electronics is emerging which can be made into wearable e-textiles. A suite of start-of-the-art functional materials have been used to develop novel fibre-based devices (FBDs), which have shown excellent potential in creating wearable e-textiles. Recent research in this area has led to the development of fibre-based electronic, optoelectronic, energy harvesting, energy storage, and sensing devices, which have also been integrated into multifunctional e-textile systems. Here we review the key technological advancements in FBDs and provide an updated critical evaluation of the status of the research in this field. Focusing on various aspects of materials development, device fabrication, fibre processing, textile integration, and scaled-up manufacturing we discuss current limitations and present an outlook on how to address the future development of this field. The critical analysis of key challenges and existing opportunities in fibre electronics aims to define a roadmap for future applications in this area.